1978
DOI: 10.5006/0010-9312-34.8.269
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Sensitization of Welded Type 304 Stainless Steel

Abstract: It has been shown that the sensitization of Type 304 stainless steel occurs at temperatures well below the normal isothermal temperature range for sensitization. A prerequisite for this low temperature sensitization (LTS) is the presence of chromium carbide nuclei along grain boundaries. This paper shows that the thermal exposure during welding can nucleate the grain boundary carbides necessary for subsequent LTS. Quantitative transmission electron microscopy studies show that no new carbides nucleate during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…Results of this analysis are illustrated in Development of low temperature sensitization can be retarded in ways other than reduction of the peak surface temperature of the container. The mechanism for development of LTS is discussed by Povich (1978) and requires a highly cold-worked structure for nucleation of subcritical carbide precipitates that are formed in the usual sensitization temperature range (above 500°C) but are not discernible by any of the ASTM tests. These subcritical precipitates then grow when the specimen is exposed to temperatures below 500°C for prolonged periods.…”
Section: Low Temperature Sensitizationmentioning
confidence: 99%
“…Results of this analysis are illustrated in Development of low temperature sensitization can be retarded in ways other than reduction of the peak surface temperature of the container. The mechanism for development of LTS is discussed by Povich (1978) and requires a highly cold-worked structure for nucleation of subcritical carbide precipitates that are formed in the usual sensitization temperature range (above 500°C) but are not discernible by any of the ASTM tests. These subcritical precipitates then grow when the specimen is exposed to temperatures below 500°C for prolonged periods.…”
Section: Low Temperature Sensitizationmentioning
confidence: 99%
“…[1][2][3][4][5] Chromium depletion in stainless steels in this temperature range progresses through both the nucleation of fresh carbides and the growth of existing carbides, if any. However, Povich et al [6,7] showed that AISI 304 at or below 500°C may get sensitized. It has also been reported that sensitization at £500°C occurs through the growth of pre-existing carbide and that fresh chromium carbide nucleation was ruled out unless specimens are coldworked to certain critical limits.…”
Section: Introductionmentioning
confidence: 97%
“…The pre-existing tiny carbide particles were observed to grow in size when failed components were investigated; this was accompanied by severe chromium depletion from adjacent grain boundaries. [6,7] Extensive intergranular stress corrosion cracking (IGSCC) failures of the recirculation pipelines in boiling water reactors were reported due to LTS. [6][7][8][9] The AISI 304L and 316L, the candidate materials for nuclear waste storage, were reported to fail from heat-affected zone (HAZ) locations by LTS-enhanced IGSCC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations